INTERACTIVE GAME SIMULATIONS AND TRAINING PLATFORMS FOR FOOTBALL GOALKEEPERS - Bobomuradov Sobitjon Erkinovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the use of interactive game simulations and digital training platforms in the development of football goalkeepers. The study examines how virtual simulations, gamified exercises, and real-time feedback can enhance technical, cognitive, and tactical skills. Additionally, the article discusses the benefits of integrating interactive platforms into training programs to optimize performance, improve decision-making, and increase engagement among goalkeepers.